Location Based Service Panduan Pencarian Rumah Sakit dengan Platform Android di Kota Semarang - Muh. Udka; R. Rizal Isnanto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Until now, the location information of the General Hospital has not yet computerized and many take advantage of mobile devices. Therefore, it is necessary to study to facilitate the search for the nearest hospital. Android-based phones have several features such as the Global Positioning System (GPS), which can be used to give the user the latest geolocation information, and connectivity with the 3G network. While the Location Based Service (LBS) are services that support GPS function. The Android platform can also be integrated with the Google Maps API. Google Maps API is a product from Google that offers the ease of building applications that require data geolocation and the ability to provide a fairly complete map. The first step in this research is to study the literature on Android, GPS, and Google Maps API. The second step is to design applications with modeling Unified Modeling Language (UML). The final step, carried implementation using the Java programming language. Based on test results, hospital In the search application, there are two options to choose a search based on a list of hospitals or radius of the location of the user. And the use of GPS is very accurate, but it can only work with a maximum when used in a location free from obstruction satellite, evident from testing conducted by researchers who carried out the entire room without any obstructions. Search applications hospital immediately shows the route to the nearest hospital from the user. At the hospital Radius of users displayed in the application is the shortest distance when the straight line drawn between the hospital with the user. Search applications hospitals can work well in the real environment, ie Android devices Sony Ericsson Xperia Arc. Android applications are developed with the target API level 15, can run well too at the API level on it.